Current Application of Unusual 3D Pedestrian Transition for Road Safety - Baghdasaryan, Irina; Barseghyan, Anzhela (Scientific Papers of National University of Architecture and Construction of Armenia, 2023)
Increasing the efficiency of the functioning of vehicles on Republic of Armenia roads, the level of high accident rate, namely collisions with pedestrians, create serious unrest. Therefore, unusual zebra crossings (of any color) are created and applied to the asphalt surface using 3D technologies that turn ordinary urban details into art objects and look like concrete blocks hanging over the road and casting a shadow on it, they are also very noticeable from afar. It is this factor that will force vehicle drivers to slow down in advance in order to let pedestrians through.